Morphometric study of the cell nucleus of endometrioid carcinoma of the uterus - Ridyl Sarduy Rodríguez; Raisel García Pérez; Norma Bárbara Hernández Pérez; Neisy Pérez Ramos; Belkis Yanes Milián; Iván Triana de la Paz (Acta Médica del Centro)
Introduction: endometrial carcinoma is among the leading causes of cancer in women and is the second most common gynecological neoplasm worldwide. Through morphometry it is possible to corroborate whether the subjective morphological interpretation and the grading obtained have been correct. Objective: to morphometrically describe the nucleus of the neoplastic cells of endometrioid carcinoma. Methods: a developmental, observational, descriptive, cross-sectional investigation was carried out at the “Mariana Grajales” Gynecobstetric Hospital in the period from November 2018 to September 2022. The sample consisted of 221 endometrial biopsy slides: 211 with diagnosis of endometrioid carcinoma and 10 of normal endometrial tissue. Results: the nuclear area and perimeter and the largest and smallest nuclear diameters had the maximum values in endometrioid carcinoma, and the mean and standard deviation of each of these morphometric parameters was greater in the carcinomatous cells. The relationship between the histological diagnosis and the circularity of the nucleus had statistical significance. Conclusions: there are quantitative differences between the morphometric variables of the normal endometrium and those of the endometrioid carcinoma, the lowest values of the morphometric parameters were observed in the glandular cells of the normal endometrium while the highest values were observed in the endometrioid carcinoma.